Keabsahan Pengangkatan Pejabat Kepala Daerah Akibat Penundaan Pemilihan Kepala Daerah - Nur Faisyah; Sudarsono Sudarsono; Shinta Hadiyantina; Irfan Amir (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2023)
This study aims to analyze the validity of the designation of acting regional heads as an implication of the postponement of the 2022 and 2023 regional elections. This research is normative, with a statutory and analytical approach. The primary legal material is Law Number 10 of 2016 concerning Regional Head Elections. Secondary legal materials are articles, books, and research findings gathered through normative research and analyzed using a research methodology. The results showed that the implication of postponing the 2022 and 2023 regional elections caused a vacancy in the position of the regional head, which had implications for the appointment of the TNI/Polri as acting regional head, which deviated from the state rule of law. Based on the decision of the Constitutional Court, the TNI/ Polri can occupy civilian positions if they retire or resign from active service and have gone through the process openly and competitively. Meanwhile, the mechanism for appointing acting regional heads from the TNI/ Polri who are still active has been contrary to the principle of the procedure for the validity of the actions of government officials. So that the government needs to immediately issue a government regulation related to the mechanism for appointing acting regional heads due to the postponement of technical regional elections so that the appointment can have a basis in the selection mechanism and qualification of acting regional heads democraticallyThis study aims to analyze the validity of the designation of acting regional heads as an implication of the postponement of the 2022 and 2023 regional elections. This research is normative, with a statutory and analytical approach. The primary legal material is Law Number 10 of 2016 concerning Regional Head Elections. Secondary legal materials are articles, books, and research findings gathered through normative research and analyzed using a research methodology. The results showed that the implication of postponing the 2022 and 2023 regional elections caused a vacancy in the position of the regional head, which had implications for the appointment of the TNI/Polri as acting regional head, which deviated from the state rule of law. Based on the decision of the Constitutional Court, the TNI/ Polri can occupy civilian positions if they retire or resign from active service and have gone through the process openly and competitively. Meanwhile, the mechanism for appointing acting regional heads from the TNI/ Polri who are still active has been contrary to the principle of the procedure for the validity of the actions of government officials. So that the government needs to immediately issue a government regulation related to the mechanism for appointing acting regional heads due to the postponement of technical regional elections so that the appointment can have a basis in the selection mechanism and qualification of acting regional heads democratically.This is an open access article under the CC–BY-SA 4.0 license.